2022
DOI: 10.53402/ajebm.v1i2.175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental performance, environmental costs, and company size on financial performance through corporate social responsibility

Abstract: low environmental management applied by the company amid the modern economic era now causes easy environmental damage. This condition must be overcome so that the company's image remains well respected and financial performance has an increasing income. Financial performance is influenced by several factors, including environmental performance, environmental costs, company size and disclosure of corporate social responsibility. This study aims to determine the effect of environmental performance, environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
1
0
0
Order By: Relevance
“…This study's findings are supported by the legitimacy theory, which suggests that strong environmental performance enhances a company's legitimacy in the eyes of investors, leading them to invest in the company and thereby increase its value. Furthermore, the results of this study are consistent with those of (Evelyn et al, 2022) and (Camilia, 2016), who concluded that environmental performance positively influences company value. However, these findings contradict the results of a study conducted by (Meiyana & Aisyah, 2019), which indicated that environmental performance does not affect company value.…”
Section: Ceo Education Has No Effect On Company Valuesupporting
confidence: 91%
“…This study's findings are supported by the legitimacy theory, which suggests that strong environmental performance enhances a company's legitimacy in the eyes of investors, leading them to invest in the company and thereby increase its value. Furthermore, the results of this study are consistent with those of (Evelyn et al, 2022) and (Camilia, 2016), who concluded that environmental performance positively influences company value. However, these findings contradict the results of a study conducted by (Meiyana & Aisyah, 2019), which indicated that environmental performance does not affect company value.…”
Section: Ceo Education Has No Effect On Company Valuesupporting
confidence: 91%